2012
DOI: 10.1007/s12262-012-0680-8
|View full text |Cite
|
Sign up to set email alerts
|

Single Port Versus Multiple Port Laparoscopic Cholecystectomy—A Comparative Study

Abstract: Single port laparoscopic cholecystectomy (SPLC) was introduced to minimize postoperative morbidity and improve cosmesis. We performed a comparative study to assess feasibility, safety and perceived benefits of SPLC. Two groups of patients (104 each) with comparable demographic characteristics were selected for SPLC and multiport laparoscopic cholecystectomy (MPLC) between May 2010 to March 2011. SPLC was performed using X cone® with 5 mm extra long telescope and 3 ports for hand instruments. MPLC was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…With respect to the mean duration of the surgical procedures, a longer operative time has been reported in the literature for single-port laparoscopic cholecystectomy. Sharma et al 28 compared the mean duration of surgical procedures and found an operative time of 26 min (15-40 min) for multiport laparoscopic cholecystectomy and of 61 min (40-120 min) for single-port laparoscopic cholecystectomy. In the study of Wagner et al 33 , the mean operative time was 60 min (33-190 min) for conventional laparoscopic cholecystectomy and 73 min (35-136 min) for single-port laparoscopic cholecystectomy, with a significant difference between procedures (p<0.001) 33 , 29 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the mean duration of the surgical procedures, a longer operative time has been reported in the literature for single-port laparoscopic cholecystectomy. Sharma et al 28 compared the mean duration of surgical procedures and found an operative time of 26 min (15-40 min) for multiport laparoscopic cholecystectomy and of 61 min (40-120 min) for single-port laparoscopic cholecystectomy. In the study of Wagner et al 33 , the mean operative time was 60 min (33-190 min) for conventional laparoscopic cholecystectomy and 73 min (35-136 min) for single-port laparoscopic cholecystectomy, with a significant difference between procedures (p<0.001) 33 , 29 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In other studies, this different was not significant. [ 4 5 ] This difference between the research works may be due to the fact that there might be other reasons other than the port size affecting this matter. The postsurgical effects were not compared between the MLC and the common method.…”
Section: Discussionmentioning
confidence: 98%
“…The surgery duration of SILC was clearly longer in most of these research works. [ 3 4 5 6 7 8 ] MLC was compared with the common method in a few studies, which indicated that the MLC method did not take a longer time period than the common method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of single incision laparoscopic cholecystectomy (SILC), this purpose is achieved in terms of cosmetic issues, but its effectiveness in providing minimal postoperative pain is still controversial (2)(3)(4)(5). Recent meta-analysis showed significantly favourable cosmetic benefits, comparable complication rates and length of hospital stay with SILC, but the mean operation time was significantly longer (6).…”
Section: Introductionmentioning
confidence: 99%